PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 026793 BINJAI - Siregar, Khopipah Indah; Prawijaya, Septian (Universitas Negeri Medan, 2024)
Abstract : The Effect of Example Non Example Model on the Learning Outcomes of IPAS Class V Students of SDN 026793 Binjai. This research aims to determine the effect of the Example Non Example learning model on the learning outcomes of IPAS (Integrated Science) for fifth-grade students at SDN 026793 Binjai. The research design used is a Quasi-Experimental Design in the form of Non-Equivalent Control Group Design. The population of this study is all fifth-grade students at SDN 026793, totaling 48 students. The research sample was taken using total sampling technique, consisting of class V-A as the experimental group and class C as the control group. Data were collected using a 20-item multiple-choice test of IPAS Topic C